2014
DOI: 10.1186/2251-6581-13-42
|View full text |Cite
|
Sign up to set email alerts
|

The cost of diabetes chronic complications among Iranian people with type 2 diabetes mellitus

Abstract: BackgroundTo evaluate the cost of diabetes related micro- and macrovascular complications in Iranian people with type 2 diabetes mellitus.MethodsIn routine clinical practice, people with type 2 diabetes mellitus were assessed for 10 years at a diabetes care center. The type of medications and clinical data were extracted from patients’ documents. Mortality rate and the incidence of micro- and macrovascular complications recorded in patients’ documents were analyzed. Cost analysis was comprised of 1) para clini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 44 publications
(54 reference statements)
0
26
0
4
Order By: Relevance
“…Patients newly diagnosed with end-stage renal [29], leading to a substantial decrease in the direct medical cost. The absolute health service costs of people with diabetes vary widely among different countries and healthcare systems [7,9,11,30], but relative costs of care for people with diabetes with a particular complication compared with an age-and sex-matched person without complications tend to vary less across different healthcare settings [6,8,11]. The multipliers of complications, rather than absolute dollar values, may be more appropriate for international comparison.…”
Section: Discussionmentioning
confidence: 99%
“…Patients newly diagnosed with end-stage renal [29], leading to a substantial decrease in the direct medical cost. The absolute health service costs of people with diabetes vary widely among different countries and healthcare systems [7,9,11,30], but relative costs of care for people with diabetes with a particular complication compared with an age-and sex-matched person without complications tend to vary less across different healthcare settings [6,8,11]. The multipliers of complications, rather than absolute dollar values, may be more appropriate for international comparison.…”
Section: Discussionmentioning
confidence: 99%
“…29 A retrospective cohort of 1000 patients with T2D demonstrated that over a period of 10 years, 10.9% developed peripheral neuropathy. 34 The 10-year incidence rates for diabetic foot ulcer, diabetic nephropathy, and ophthalmologic complications including retinopathy were 8%, 4.6%, and 9.1%, respectively. 34 Selected studies on the prevalence of diabetes complications are summarized in Table 1.…”
Section: E P I D E M I O L O G Y O F D I a B E T E S A N D I T S C O mentioning
confidence: 98%
“…For example, Woung et al (2010) reported significant increase of costs associated with diabetic retinopathy (US $1566in 2000to US $3326 in 2004). Some studies also were limited to incremental costs between diabetic cohort and their non-diabetic counterparts only (Brown, Pedula, & Bakst, 1999;Farshchi, Esteghamati, Sari, et al, 2014;Straka et al, 2009;Woung et al, 2010).…”
Section: Introductionmentioning
confidence: 98%
“…Furthermore, most longitudinal studies only included diabetic patients free of complications but not diabetic patients with different severity of complications at cohort entry (Farshchi et al, 2014;Woung et al, 2010). In addition, some of the existing studies were limited to data derived from simulation models (Zhuo, Zhang, & Hoerger, 2013) instead of "real-world" data (Brandle et al, 2003;Caro, Ward, & O'Brien, 2002).…”
Section: Introductionmentioning
confidence: 99%